Multiple Magma Storage Regions and Open System Processes Revealed by Chemistry and Textures of the Datong Tholeiitic Lavas, North China Craton. (5th April 2022) - Pan, Ronghao; Hou, Tong; Wang, Xudong; Encarnación, John; Botcharnikov, Roman
ABSTRACT: The geochemistry of lavas combined with textural constraints can provide important information on magmatic processes occurring at inaccessible depths. Here we carry out a detailed textural and geochemical study on 0.23 Ma contemporaneous and adjacent Qiulin, Longbao, and Dayukou volcanoes in the intraplate Quaternary Datong volcanic field (DVF) in the North China Craton. Lavas from the three tholeiitic volcanoes have similar major and trace element compositions with their trace element patterns resembling enriched mid-ocean ridge basalts (E-MORB). However, distinct textures are observed between the samples from the three volcanoes. Samples from Qiulin are generally poorly-phyric (<10 vol. %) containing orthopyroxene, plagioclase, and olivine phenocrysts and monomineralic orthopyroxene glomerocrysts set in a groundmass of plagioclase, clinopyroxene, orthopyroxene, and Fe–Ti oxides. In contrast, samples from both Longbao and Dayukou are highly phyric (up to ~50 vol. %) and consist mainly of plagioclase, orthopyroxene, clinopyroxene, and olivine phenocrysts with mm- to cm-sized polymineralic glomerocrysts enclosed in a groundmass comprising plagioclase, clinopyroxene, olivine, and Fe–Ti oxides. Crystal types and proportions vary significantly between the glomerocrysts of Longbao and Dayukou even on a thin section scale. The phenocrysts and glomerocrysts at the two volcanoes commonly show resorbed and embayed margins and sieve textures. Moreover, pyroxenes present as phenocrysts and glomerocrysts are always characterised by corona textures containing orthopyroxene cores mantled by clinopyroxene. Notably, orthopyroxene is never observed in contact with groundmass. The relatively low Mg# (75–85) and Ca content in the cores indicate that the orthopyroxenes from all three volcanoes are crystallised early from the magma rather than being mantle xenocrysts. Thermobarometry and kernel density estimation indicate that orthopyroxenes in all three volcanoes initially crystallised at ~7 kbar (23 km depth), whereas clinopyroxenes crystallised at ~4 kbar (13 km) and the final crystallisation pressure is ~3 kbar (10 km). Thermodynamic modelling by COMAGMAT suggests early near-liquidus crystallisation of the orthopyroxene at high pressures, followed by partial dissolution likely associated with decompression. The relatively larger proportions of phenocrysts compared with glomerocrysts in Qiulin samples implies that the magma reservoir was only partially turned into mushes at the periphery. Magma ascending via the melt-rich interior of the magma reservoir formed the crystal-poor Qiulin lava. In contrast, those ascending through the mushes at the peripheries of the deeper reservoir and discrete shallower storage regions formed the highly phyric Longbao and Dayukou lavas. The pervasive occurrence of sieve textures and complex mineral composition profiles in both phenocrysts and glomerocrysts in Longbao and Dayukou samples belie complicated open system crystallisation histories of these magmas. We conclude that open system processes involving mush disaggregation and magma recharge in multi-level plumbing systems played an important role in the petrogenesis of these intracontinental tholeiites. Moreover, the important role of orthopyroxene in the petrogenesis of these tholeiites distinguishes them from many other tholeiite suites like MORB, as well as those erupted through thickened oceanic crust like in Iceland and the Shatsky Rise. This study highlights the importance of combining textural constraints with geochemical analyses.